CREATION OF A PLATFORM FOR INFORMATION SECURITY RISK ANALYSIS AND MANAGEMENT - Adilzhanova, С.А.; Abdulkarimova, Г.А.; Gusmanova, Ф.Р.; Zhubanysheva, Г.Т. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2025)
This article is devoted to the development of a platform for the analysis and management of information security risks arising from the use of digital twin technology. The study examines the role and importance of digital twins in Industry 4.0, especially in areas such as manufacturing, energy, smart cities, and cyber-physical systems. The risks associated with information security and their causes will be identified, as well as ways to reduce them. Innovative methods such as predictive analysis, artificial intelligence, adaptive security systems, cryptographic technologies and blockchain are being discussed, which will enhance the security of digital twin platforms and ensure information security. These methods are important tools for improving the reliability of Gemini digital systems, and their integration contributes to improving the efficiency and security of the platforms. As a result, digital twins are used to improve the efficiency of system management by ensuring their security, optimizing business processes and opening up new opportunities. In addition, these methods ensure compliance with information security requirements and long-term stability of digital twin platforms.